The Influence of Quranic Education on Discipline and Responsibility Among Students at Integrated Islamic Elementary Schools in Rokan Hulu Regency - Hamdi Pranata; Nofiardi Nofiardi; Salmi Wati; Elbina Mamla Sa’idah; Romi Maimori; Habibuddin Habibuddin; Sulaiman Sulaiman; Khairul Firdaus (International Journal of Educational Narratives, 2026)
Background. Character formation in Islamic elementary education requires pedagogical practices that are not only instructional but also narrative, value-oriented, and behaviorally observable. In Islamic integrated schools, Qur’anic education functions as a narrative medium through which moral stories, religious meanings, teacher modeling, and daily routines are transmitted to students. Purpose. This study analyzed the predictive effect of Qur’anic educational narratives on students’ discipline and responsibility at SD IT Al-Bayan Islamic School, Tambusai District, Rokan Hulu Regency. Method. This study employed a quantitative explanatory survey design involving all 115 students (62 male, 53 female), using total sampling as the entire population was accessible. Data were collected via a five-point Likert questionnaire measuring Qur’anic educational narratives, discipline, and responsibility, analyzed using descriptive statistics, validity/reliability testing, normality and linearity tests, Pearson correlation, and simple linear regression. Results. Qur’anic educational narratives positively and significantly predicted students’ discipline (R = 0.522; R² = 0.273; p < .001) and responsibility (R = 0.388; R² = 0.151; p < .001). The predictive effect on discipline was stronger than on responsibility, indicating that routine, teacher-guided, narratively reinforced Qur’anic practices more directly shape punctuality, rule obedience, orderly participation, and task completion. Conclusion. Qur’anic educational narratives serve as a measurable narrative-based character-building strategy strengthening discipline and responsibility through recitation, storytelling, teacher modeling, and behavioral evaluation, implying that programs should connect religious routines with observable character indicators.